Analyzing Tumor Budding Scores in Invasive Breast Carcinoma: A Tertiary Care Center Study in South India - Vasudevan Sudha; Kannan Kavitha; Raghavan ATM Venkat; Sulochana Sonti (Wolters Kluwer Medknow Publications, 2024)
Introduction and AimTumor budding is a distinctive phenomenon which involves the presence of small clusters or individual cancer cells at the invasive front of tumors. Tumor budding has garnered attention due to its potential implications for prognosis, treatment strategies, and our understanding of cancer progression. Our aim is to study the distribution of tumor buds and its scoring in patients with infiltrating breast carcinoma and to associate with other histopathological parameters like the size of the tumor, its grade, lymphovascular invasion, and lymph node metastasis. Materials and MethodsThis was a study analyzing the data of 70 resected specimens of primary breast carcinomas and providing a descriptive overview. Tumor budding was recognized, counted, and graded in hematoxylin and eosin slides. The cases were classified as low (0-4), intermediate (5-9), and high (≥10 buds) based on the count of tumor buds. Tumor budding has significant correlation with tumor grade and tumor size. ResultsOf the 70 cases, 60 cases (85.71%) were diagnosed as invasive ductal carcinoma NOS. The majority [38 (54.28%)] of the cases showed an intermediate tumor budding score of 5-9/10 HPF. ConclusionEvaluation of tumor budding allows pathologists and oncologists to gather valuable information about the tumor's biological aggressiveness and potential for metastasis. It also helps in better risk stratification of patients, enabling a more personalized and tailored approach to treatment planning. In conclusion, assessing tumor budding in breast carcinoma holds significant clinical importance in the management and prognosis of this disease.